(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Small and medium-sized road transport companies located in Croatia are faced with strong competition on the transport and logistics market. The problem of cost management in road transport enterprises is one of the most crucial ones for their efficient functioning. Enterprises operating on the market are very different, so it is important to analyse their cost structure in relation to their organization. To improve the system and reduce transport costs, a multi-level full cost allocation model has been set up and is analysed in this paper. The authors give an overview of the research results on the costs structure of a road transport company from Zagreb and present their components and differences. The authors establish and present the differences in the cost structure and the impact of costs on the optimization of transport routes and logistics management.